The Effectiveness of Different Insole Material in Plantar Pressure Reduction : a Pilot Study - Shuib, Solehuddin; Salwa Ahmad, Anis; Rahman Omar, Abdul; Faiz Borhanuddin, Muhammad; Hanif Ahmad Hamidi, Shahfuan (International Journal of Engineering and Technology, 2018)
Standing is natural human position which is an upright body position against gravity and supported only by feet. It normally caused no health hazard. However, frequent standing together with awkward standing postures may cause discomfort to the foot. This is due to higher value of plantar pressure under the foot and in the long run, its can leads to other health problems such as musculoskeletal disorder. Therefore, insole is believed to have capacity to reduce the plantar pressure under the foot by redistribute the pressure. The use of insole to reduce the plantar pressure has been well document in previous study but very little data reported on assessment among healthy subjects. Hence, the purpose of the study is to evaluate the effects of four different types of insole materials using plantar pressure measurement. The material uses in this study are ethyl vinyl acetateÂ (EVA), Polyurethane (PU), Polyester and Polyurethane with gel (PU gel). Four healthy male volunteer with age mean and SD (24Â±1.7) years and weight (66Â±0.82) kg is required to stand in an upright position with minimal movement allowed. The comparison of four insoles with barefoot condition shows that PU insole is the most effective material because it can reduce 16.28% of plantar pressure.Â Â